Carbon footprint awareness of nursing students: a qualitative study - Mağfiret Kaşıkçı; Yeşim Bağcı; Zeynep Yıldırım; Ulviye Aydan Nacak (BMC Nursing)
Abstract Backround The increasing impact of climate change on public and environmental health underscores the importance of understanding carbon footprints and adopting sustainable practices. Nursing students play a critical role in promoting environmental awareness and integrating eco-friendly practices into healthcare delivery. This study aims to assess nursing students’ awareness of the ‘Carbon Footprint’ and their suggestions for reducing their carbon footprint. Design Qualitative study. Methods Twelve fourth-year nursing students enrolled in the “Public Health Nursing” course within the nursing department from a university located in eastern Turkey participated in this study. Twelve face-to-face interviews were conducted. Transcripts were subjected to structured qualitative content analysis. Results As a result of the analysis of the data obtained from the participants, two main themes as ‘Perceived Impacts of Carbon Footprint’ and ‘Carbon Footprint Reduction Strategies’, four sub-themes as ‘Perceived Impact on Human Health’, ‘Perceived Impact on Environmental Health’, ‘Recommended Individual Strategies’ and ‘Recommended Institutional-Level Strategies’ and eighteen codes in total were created. Conclusion This study revealed that nursing students possess a fundamental awareness of the carbon footprint and its implications for human and environmental health. Integrating comprehensive environmental education into nursing curricula can empower future healthcare professionals to adopt and advocate for sustainable practices in both personal and professional domains.